Austenite evolution and quantification in aged 250 maraging steel: A comparative analysis of X-ray diffraction methods - Fábio Lima da Silva; Julianna Magalhães Garcia; Alaelson Vieira Gomes; Luiz Paulo Mendonca Brandao (Journal of Materials Research and Technology, 2025)
This study investigates the quantification of reversed austenite in a 250-grade maraging steel aged at different temperatures using X-ray diffraction (XRD). Two-phase quantification techniques, direct comparison method (DCM) and Rietveld refinement were employed to determine the austenite fraction. The results indicate that austenite reversion begins at 490 °C, accelerates beyond 530 °C, and stabilizes at higher temperatures, where austenite becomes the dominant phase. Deviations between the two quantification methods at elevated temperatures are attributed to precipitation effects, though DCM remains reliable despite the presence of precipitates. To validate the XRD-based quantification, scanning electron microscopy (SEM) was employed to assess the microstructural evolution, revealing the progressive formation of reversed austenite along prior austenite grain boundaries and martensite packets at temperatures of 520 °C and 600 °C. Mechanical testing, including compression and tensile experiments, demonstrated that ultimate tensile strength (UTS) and yield strength increase with the initial rise in austenite fraction, peaking within the 12–18 % range. However, when the austenite fraction exceeds 80 %, a significant reduction in mechanical strength occurs due to the inherently ductile nature of austenite. To further investigate the microstructure, particularly the precipitates, TEM images were obtained at 520 °C and 600 °C—temperatures corresponding to the peak mechanical strength and the overaging stage, respectively. Transmission electron microscopy (TEM) coupled with energy-dispersive X-ray spectroscopy (EDS) enabled elemental analysis at both aging temperatures, providing insight into the precipitate size distribution. This study provides a comprehensive understanding of austenite evolution, integrating XRD phase quantification, SEM and TEM microstructural characterizations, and mechanical performance analysis to optimize aging treatments in 250-grade maraging steel.